Swine Enteric Coronaviruses (PEDV, TGEV, and PDCoV) Induce Divergent Interferon-Stimulated Gene Responses and Antigen Presentation in Porcine Intestinal Enteroids - Yin, Lingdan; Liu, Xiang; Hu, Dongmei; Luo, Yi; Zhang, Guozhong; Liu, Pinghuang (Frontiers in Immunology, 2022)
Swine enteric coronaviruses (SECoVs) including porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), and porcine deltacoronavirus (PDCoV), account for the majority of lethal watery diarrhea in neonatal pigs and pose significant economic and public health burdens in the world. While the three coronaviruses primarily infect intestinal epithelia in vivo and cause similar clinical signs, there are evident discrepancies in the cellular tropism and pathogenicity among the three SECoVs infections. However, the underlying mechanisms to cause the differences remain unclear. Herein, we employed porcine enteroids that are a physiologically relevant model of the intestine to assess the host epithelial responses following infection with the three SECoVs (PEDV, TGEV, and PDCoV). Although SECoVs replicated similarly in jejunal enteroids, a parallel comparison of transcriptomics datasets uncovered that PEDV and TGEV infection induced similar transcriptional profiles and exhibited a more pronounced response with more differentially expressed genes (DEGs) in jejunal enteroids compared with PDCoV infection. Notably, TGEV and PDCoV induced high levels of type I and III IFNs and IFN-stimulated gene (ISG) responses, while PEDV displayed a delayed peak and elicited a much lesser extent of IFN responses. Furthermore, TGEV and PDCoV instead of PEDV elicited a substantial upregulation of antigen-presentation genes and T cell-recruiting chemokines in enteroids. Mechanistically, we demonstrated that IFNs treatment markedly elevated the expression of NOD-like receptor (NLR) family NLRC5 and major histocompatibility complex class I (MHC-Ⅰ) molecules. Together, our results indicate unique and common viral strategies for manipulating the global IFN responses and antigen presentation utilized by SECoVs, which help us a better understanding of host-SECoVs interactions.